Should I stay or should I go? The feelings expresses by teachers about their retirement - Ana Claudia Oliveira Hopf (Journal of Physical Education (Maringá), 2008)
This study had as a main point to identify the University teachers feelings expressed in their last years of work. The attitudes the idea of retirement and the disconnect of the responsibility that they’re use to. The research was made with eight male Physical Education teachers. The information process was made half-structure interview. Teachers had showed in their depositions satisfaction feelings about their career. Soon teachers continued working and studying but there are some teachers that retired themselves without thinking in what to do after their legal University occupation disconnection.